2018
DOI: 10.1080/01443615.2017.1380612
|View full text |Cite
|
Sign up to set email alerts
|

A questionnaire survey of second year graduate-entry medical students’ perception of obstetrics and gynaecology as a future career speciality

Abstract: The aim of this study was to explore the impressions of second year graduate-entry medical students of Obstetrics and Gynaecology, before their attachment in the speciality in the subsequent year, so as to improve its appeal to them and increase their recruitment into it. A total of 74 questionnaires were distributed at the end of the Learning Opportunities in Clinical Setting (LOCS) week in the speciality and 66 (89.19%) completed questionnaires were returned. Over 4% of the respondents were considering the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…A semi-structured questionnaire (Appendix S1) was developed with members of the GEDWG and based around similar surveys developed in Australian and overseas studies. [1][2][3] Randomised computer-generated selection was used to identify the research subjects. Students were invited by email to participate in a one-to-one semi-structured telephone interview, based around the questionnaire, between 1 July and 31 December 2020.…”
Section: Methodsmentioning
confidence: 99%
“…A semi-structured questionnaire (Appendix S1) was developed with members of the GEDWG and based around similar surveys developed in Australian and overseas studies. [1][2][3] Randomised computer-generated selection was used to identify the research subjects. Students were invited by email to participate in a one-to-one semi-structured telephone interview, based around the questionnaire, between 1 July and 31 December 2020.…”
Section: Methodsmentioning
confidence: 99%
“…Interest in gynaecology only as a rst choice, while increasing from a very low base, remained low at 4.2%, demonstrating a clear preference amongst students for obstetrics. [14] These gures are signi cantly higher than international comparators. A survey conducted in Switzerland showed that 5.9% of fourth year residents were interested in a career in Obstetrics and Gynaecology.…”
Section: Discussionmentioning
confidence: 91%
“…[12] In two studies of graduate entry medical students in Wales published in 2014 and 2020, Ismail and Kevelighan found that 4% and 3.9% would consider the speciality as rst career choice respectively. [14,20] The low interest levels in obstetrics and gynaecology internationally are a concern given the need to increase recruitment into the specialism(s) and leads to considerations of why the speciality is not more attractive. In an Irish context, the increased interest postrotation is encouraging, placing us in a better position than colleagues internationally to meet future demand and leading to considerations of the availability of training opportunities to meet demand amongst this cohort.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations